TNFRSF17 as a complementary biomarker to PD-L1 for predicting the response to immunotherapy in urothelial bladder cancer - Jiawen Chen; Bingsheng Li; Yu Gan; Pan Li (PLoS ONE, 2026)
Background Programmed death-ligand 1 (PD-L1) positivity is associated with a favorable response to immune checkpoint blockade (ICB) in urothelial bladder cancer (BLCA). However, the efficacy of ICB in BLCA exhibits considerable heterogeneity, leading to the need for complementary predictive biomarkers. Recent studies suggest that a high degree of plasma cell infiltration is correlated with improved benefit from ICB, but a specific plasma cell marker in BLCA has not been identified. The aim of this study was to evaluate tumor necrosis factor receptor superfamily member 17 (TNFRSF17) as a plasma cell-specific marker in BLCA and test its utility, combined with PD-L1, for patient stratification receiving ICB therapy. Methods Transcriptomic and clinical data from publicly available cohorts were analyzed. Plasma cell-associated markers were identified based on expression specificity and correlation analyses. The clinical relevance of TNFRSF17, alone and in combination with CD274, was evaluated by comparisons of survival and the response rate. Associations with immunotherapy-related features were examined using established surrogate measures, including the immunophenoscore. In silico deconvolution analyses were performed to characterize the immunogenic tumor microenvironment by comparing distinct immune infiltration patterns and differential gene expression pathways between the subgroups. Results Plasma cell infiltration correlated with favorable survival in BLCA patients. Higher expression of TNFRSF17, a plasma cell-specific marker (R = 0.73 ± 0.15; z score = 1.88 ± 0.41), correlated with increased immunophenoscores, more favorable overall survival outcomes (HR = 0.59) and increased responsiveness to ICB therapy. Tumors with concurrent high TNFRSF17 and CD274 expression exhibited the most favorable survival outcomes (HR = 0.38) and demonstrated an immune-inflamed transcriptional profile, including enrichment of antigen presentation and immune signaling pathways. Conclusions TNFRSF17 serves as a potential marker to characterize an immune-distinct and prognostically favorable subgroup within CD274High tumors, and to refine stratification for ICB.